Comparison of neoadjuvant chemotherapy or chemoradiotherapy plus immunotherapy for locally resectable esophageal squamous cell carcinoma - Yang, Guozhen; Yue, Haodong; Zhang, Xiaomin; Zeng, Chufeng; Tan, Linyu; Zhang, Xu (Frontiers in Immunology, 2024)
Neoadjuvant chemotherapy plus immunotherapy (nCT + ICIs) and neoadjuvant chemoradiotherapy plus immunotherapy (nCRT + ICIs) both induced favorable pathological response and tolerant toxicities for locally resectable esophageal squamous cell carcinoma (ESCC). However, few studies compared safety and efficacy between the two treatment strategies.This retrospective study collected clinical data of locally resectable ESCC patients who underwent nCT + ICIs or nCRT + ICIs followed by esophagectomy from November 2019 to December 2022. The incidence of adverse events, surgical outcomes, short and long-term efficacy, and treatment costs were compared.A total of 206 patients were included, with a ratio of 158:48 between nCT + ICIs group and nCRT + ICIs group. The two groups exhibited well-balanced baseline characteristics. Most adverse events were grade 1-2 in both groups. The nCT + ICIs group had a longer operative time (334.00±170.2 min vs 279.60±88.31 min, p=0.020) than nCRT + ICIs group, but there were no differences in surgical complications.Although nCT + ICIs group had a lower pCR rate (32.3% vs 52.1%, p=0.004), the 2-year overall survival (84.42% vs 81.70%, p=0.860), 2-year disease-free survival (83.21% vs 80.47%, p=0.839), and recurrence patterns were similar to nCRT + ICIs group. In addition, nCT + ICIs group had significantly lower expenses (188796.00±107704.00 RMB vs 231808.00±48067.00 RMB, p=0.045).Overall, nCT + ICIs have comparable safety and efficacy compared to nCRT + ICIs for locally resectable ESCC, but with lower hospitalization costs.